2010
DOI: 10.1007/s11590-010-0183-0
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness of integer solution of linear equations

Abstract: Abstract. We consider the system of m linear equations in n integer variables Ax = d and give sufficient conditions for the uniqueness of its integer solution x ∈ {−1, 1} n by reformulating the problem as a linear program. Uniqueness characterizations of ordinary linear programming solutions are utilized to obtain sufficient uniqueness conditions such as the intersection of the kernel of A and the dual cone of a diagonal matrix of ±1's is the origin in R n . This generalizes the well known condition that ker(A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This problem, which has also been studied in [12], can be considered a generalization of the classical knapsack feasibility problem [11,7,4] of finding an n-dimensional binary integer vector y ∈ {0, 1} n such that:…”
Section: Introductionmentioning
confidence: 99%
“…This problem, which has also been studied in [12], can be considered a generalization of the classical knapsack feasibility problem [11,7,4] of finding an n-dimensional binary integer vector y ∈ {0, 1} n such that:…”
Section: Introductionmentioning
confidence: 99%
“…In that sense in [15] and [16] it is proved that the probability that a linear relaxation system of an integer one of the form given in (3) returns a unique integer solution, increases and approaches to 1 when the relationship between the number of constraints (measurements, m = |T|) and the number of variables (customers, n = |I|), or m/n ratio, is greater than a given threshold.…”
Section: The (Noisy) Problem With Energy Losses or Inputsmentioning
confidence: 99%
“…Mangasarian et al [18,19] have showed that when m > n/2, a system of the form (6) has a unique solution ∈ [−1, 1] n with high probability (w.h.p). For our problem, this implies that as m crosses n/2, (6) will start to retrieve the true underlying solution to the lc problem w.h.p.…”
Section: Lemma 1 If (6) Returns An Integer Solution That Solution Imentioning
confidence: 99%